Dental management of patients with epilepsy: a literature review (Research, Society and Development, 2022)
Epilepsy is the neurological disorder with the highest incidence, the most common being, not presenting specific oral and dental characteristics. A literature review was conducted using articles from indexed databases between 2009 and 2022. It is necessary that the dentist is able to propose care to patients with epilepsy, because, although dental management does not have so many particularities, some need to be well established: the correct use of anesthetics, the correct positioning in the chair, correct action if the patient has a seizure during care, the correct management of periodontal tissues if they are hyperplasia due to the use of anticonvulsants and the  correct indication of treatments, therefore, it is concluded that the dentist should be able to attend to such patients and know the care and approaches necessary in case of crises during dental care.